INDUKSI TUNAS IN VITRO JERUK SIAM (Citrus nobilis Lour.) ASAL KAMPAR DARI EKSPLAN TUNAS APEKS DAN NODUS IN VITRO - Nurul Hidayati; Wahyu Lestari; Mayta Novaliza Isda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Citrus nobilis Lour. is a citrus plant that is highly demanded by many people in Riau. Propagation of C. nobilis Lour. has some problems due to various diseases that decrease its production. The conventional propagation of C. nobilis. requires a lot of parent plants and takes a long time, therefore the in vitro propagation is necessary. The purpose of this study was to determine the concentration of BAP and explant source as well as the interaction between both treatments in inducing C. nobilis bud. This research used a factorial randomized block design (RBD) with two factors i.e the concentration of BAP (0, 1, 2 and 3 mg / l) and the source of explants (shoot apex and 6 week in vitro nodes). All combined treatments showed no significant difference to the emerging bud, the number of shoots and length of shoot. The results showed that the addition of 2 mg/l BAP at the apex shoot and node explants were able to induce bud. Better explant sources in inducing bud was the node explants. The node explants at a concentration of 1 mg/l BAP gave better result in inducing bud.